Patient-reported long-term outcome following allogeneic hematopoietic stem cell transplantation in pediatric chronic myeloid leukemia - Schleicher, Oliver; Horndasch, Annkathrin; Krumbholz, Manuela; Sembill, Stephanie; Bremensdorfer, Claudia; Grabow, Desiree; Erdmann, Friederike; Karow, Axel; Metzler, Markus; Suttorp, Meinolf (Frontiers in Oncology, 2022)
Background: Data on the long-term outcome and health-related quality of life (HRQOL) in former pediatric patients with chronic myeloid leukemia (CML) undergoing hematopoietic stem cell transplantation (HSCT) are lacking.. Methods: Individuals with pediatric CML enrolled into previous pediatric CML-HSCT trials were identified from the German Childhood Cancer Registry. Long-term survivors received a questionnaire based on the SF-36 and FACT-BMT asking to self-report HRQOL issues. Results: 111/171 (65%) transplanted patients survived long-term and 86/111 (77%) received the questionnaire when fulfilling all inclusion criteria. 37/86 (43%) participants (24 female, 13 male, median age at HSCT 12 years [range 2-19], median age at the time of the survey 29 years [range 18-43]) responded after a median follow-up period of 19 years (range 4-27) after HSCT. 10/37 (27%) participants underwent no regular medical follow-up examinations. Self-reported symptoms comprised lung problems, dry eyes, skin alterations, hair problems, hypothyroidism, infertility, and regular occurring sexual dysfunction. 10 (27%) participants experienced 13 CML relapses after a median interval from HSCT of 31 months (range 2-93). Only one patient underwent second SCT after TKI failure of relapse treatment. Six secondary malignancies developed in five (13%) participants. Impaired physical health was mainly associated with chronic graft versus host disease (cGvHD). The mental SF-36 component summary score showed that also participants without cGvHD scored significantly lower than the general population. When assessed by the FACT-BMT, participants with cGvHD scored significantly lower while participants without cGvHD scored in the range of controls. Eighteen (49%) participants considered HSCT an educational obstacle. Out of the total cohort, N=20 (54%), N=7 (19%), N=5 (14%), and N=4 (11%) participants worked full time, part-time, were unemployed, or had not yet finalized their education, respectively. Social status comprised 54% singles, 22% participants living in a partnership, 16% were married, and 8% had been divorced. Four (11%) participants reported a total number of seven children. Conclusion: HRQOL-assessment in former pediatric CML patients who underwent HSCT two decades ago demonstrates self-reported satisfactory well-being only in the absence of cGvHD. Research based on self-reported outcome sheds light on former patients’ perspectives and provides valuable knowledge for both pediatric and adult hematologists.